EXPERIMENTAL INVESTIGATION OF MECHANICAL PROPERTIES OF UNTREATED NEW AGAVE ANGUSTIFOLIA MARGINATA FIBER REINFORCED EPOXY POLYMER MATRIX BIO-COMPOSITE MATERIAL (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In recent years, the natural fibers playing a vital role in worldwide. The main purpose of using natural fiber is biodegradable, cost wise low, easily available and at the same time strength to weight ratio is high. In this work, the Agave Angustifolia Marginata fibers (AAMFs) reinforced composite were made by compression molding machine (CMM) with various proportions of epoxy resin. The manufactured composite laminates were tested through the tensile, flexural, Impact and compression test according to ASTM standards. The results indicated that the composite with 35 weight percentage of the fibers having superior mechanical properties. The compression properties were improved in the 60:40 ratios. The surface morphology shows the great attachment or bonding was not seen between the fibers and epoxy as appeared in 60:40 proportion of composite. The strength of the fiber and composites will definitely improve after the best chemical treatment process